Intrinsic scaling for pde's with an exponential nonlinearity - Henriques, Eurica (2004)
We consider strongly degenerate equations in divergence form of the type ∂tu − ∇ • (|u|γ(x,t)∇u)= f , where the exponential nonlinearity satisfies the condition 0 < γ− ≤ γ(x, t) ≤ γ+. We show, by means of intrinsic scaling, that weak solutions are locally continuous.